2004
DOI: 10.1002/bip.20110
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and photophysical behavior of conformationally constrained hexapeptides functionalized with a new fluorescent analog of tryptophan and a nitroxide radical quencher

Abstract: The influence of the conformational properties on the photophysics of two de novo designed hexapeptides was studied by spectroscopic measurements (ir, NMR, steady-state, and time resolved fluorescence) and molecular mechanics calculations. The peptide sequences comprise two nonproteinogenic residues: a beta-(1-azulenyl)-L-alanine (Aal) residue, obtained by formally functionalizing the Ala side chain with the azulene chromophore, and a Calpha-tetrasubstituted alpha-amino acid (TOAC), incorporating a nitroxide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Mutation of Trp to AzAla has been shown to have a minimal effect on efficacy of short peptides targeting GPCR receptors in cell assays, 13 but the biophysical characterization of this probe was limited to studies of its interaction with synthetically introduced free radicals. 1416 Here we demonstrate that AzAla’s insensitivity to the environment allows for investigation of biophysical phenomena by via a structurally conservative, single fluorescent probe, which does not require additional functionalization. Together with AzAla’s similarity to Trp, it provides a powerful chemical biology tool for looking at protein-protein interactions.…”
mentioning
confidence: 73%
“…Mutation of Trp to AzAla has been shown to have a minimal effect on efficacy of short peptides targeting GPCR receptors in cell assays, 13 but the biophysical characterization of this probe was limited to studies of its interaction with synthetically introduced free radicals. 1416 Here we demonstrate that AzAla’s insensitivity to the environment allows for investigation of biophysical phenomena by via a structurally conservative, single fluorescent probe, which does not require additional functionalization. Together with AzAla’s similarity to Trp, it provides a powerful chemical biology tool for looking at protein-protein interactions.…”
mentioning
confidence: 73%
“…The results confirmed previous findings showing that Afc may adopt either a fully extended or a turn conformation. In another study, Venanzi et al (2004) used FTIR, NMR, steady-state and time-resolved fluorescence, and molecular mechanics to investigate constrained hexapeptides containing a fluorescent analogue of tryptophan as well as TOAC.…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…Rueeger et al [15] reported that (5,6-dihydro-4H-3-thia-1-aza-benzo[e]azulen-2-yl) -piperidin-4-ylmethyl-amino and (4,5-dihydro-6-oxa -3-thia-1-azabenzo[e]azulen-2-yl)-piperidin-4 -ylmethyl-amino derivatives are capable of delivering potent and selective orally and centrally bioavailable NPY-Y5 receptor antagonists. The antioxidant activity of azulene derivatives may be due to their interaction with nitroxyl radicals [230,231]. Guaiazulene is used to prevent or treat any type of hypercholesterolemia, hyperlipidemia and any other lipid disorder, atherosclerosis or atheromatosis in humans and animals because it can induce a significant reduction of total cholesterol, total triglycerides and of LDL-cholesterol level but without showing any signs of toxicity or side effects on the tested animals [232].…”
Section: Azulene and Its Derivativesmentioning
confidence: 99%